BRCA1‐like profile predicts benefit of tandem high dose epirubicin‐cyclophospamide‐thiotepa in high risk breast cancer patients randomized in the WSG‐AM01 trial. Issue 4 (5th May 2016) - Schouten, Philip C.; Gluz, Oleg; Harbeck, Nadia; Mohrmann, Svjetlana; Diallo‐Danebrock, Raihana; Pelz, Enrico; Kruizinga, Janneke; Velds, Arno; Nieuwland, Marja; Kerkhoven, Ron M.; Liedtke, Cornelia; Frick, Markus; et al.
Abstract : BRCA1 is an important protein in the repair of DNA double strand breaks (DSBs), which are induced by alkylating chemotherapy. A BRCA1 ‐like DNA copy number signature derived from tumors with a BRCA1 mutation is indicative for impaired BRCA1 function and associated with good outcome after high dose (HD) and tandem HD DSB inducing chemotherapy. We investigated whether BRCA1 ‐like status was a predictive biomarker in the WSG AM 01 trial. WSG AM 01 randomized high‐risk breast cancer patients to induction (2× epirubicin‐cyclophosphamide) followed by tandem HD chemotherapy with epirubicin, cyclophosphamide and thiotepa versus dose dense chemotherapy (4× epirubicin‐cyclophospamide followed by 3× cyclophosphamide‐methotrexate‐5‐fluorouracil). We generated copy number profiles for 143 tumors and classified them as being BRCA1 ‐like or non‐ BRCA1 ‐like. Twenty‐six out of 143 patients were BRCA1 ‐like. BRCA1 ‐like status was associated with high grade and triple negative tumors. With regard to event‐free‐survival, the primary endpoint of the trial, patients with a BRCA1‐ like tumor had a hazard rate of 0.2, 95% confidence interval (CI): 0.07–0.63, p  = 0.006. In the interaction analysis, the combination of BRCA1 ‐like status and HD chemotherapy had a hazard rate of 0.19, 95% CI: 0.067–0.54, p  = 0.003. Similar results were observed for overall survival. These findings suggest that BRCA1 ‐like status is a predictor for benefit of tandem HD chemotherapy with epirubicin‐thiotepa‐cyclophosphamide. Abstract : What's New? BRCA1 is key to the repair of DNA double‐strand breaks, such that its deficiency, as in BRCA1 ‐deficient breast cancer, renders tumors susceptible to DNA damage induced by high‐dose (HD) alkylating chemotherapy. For high‐risk, stage III breast cancer (HRBC) patients, however, HD chemotherapy is controversial due to its treatment burden and no strong benefit in the general breast cancer population. This study shows that HRBC patients whose tumors present a BRCA1 ‐like signature—a pattern of copy number aberrations characteristic of BRCA1 deficiency—experience greater improvements in survival after tandem HD chemotherapy versus conventional dose‐dense chemotherapy. Non‐ BRCA1 ‐like patients did not benefit to the same degree. The study validates and extends previous findings.